Work-up and management of paediatric Cushing's syndrome. - Savage, M; Chan, L; Grossman, AB; Storr, H (2008)
PURPOSE OF REVIEW: Paediatric Cushing's syndrome presents a diagnostic and therapeutic challenge. Most paediatric endocrinologists have limited experience in managing children or adolescents with Cushing's syndrome and thus benefit from close consultation with adult colleagues. A protocol for investigation of the child with suspected Cushing's syndrome is presented followed by principles of management. RECENT FINDINGS: Cushing's syndrome is rare in childhood, but causes serious morbidity. Investigations have evolved and now include new genetic and imaging techniques as well as classical endocrine studies. In Cushing's disease trans-sphenoidal surgery has transformed management, although only a few surgeons have experience in children. Pituitary radiotherapy is effective second-line therapy. SUMMARY: Early diagnosis and treatment of Cushing's syndrome is vital for long-term outcome. The overall prognosis for Cushing's syndrome is good but challenges remain to ensure normal postcure growth and body composition.